Exploring the experience of Racialisation and subsequent experiences of psychological therapy for Black and Multi-ethnic clients in Ireland - Doyle, Karen M.; Hannigan, Barbara (European Journal for Qualitative Research in Psychotherapy, 2024)
Research suggests pervasive disparities in mental health diagnoses, levels of care and treatment outcomes for Black or Multi-ethnic service users compared to white service users. This study explores the mental health implications of being racialised and subsequent experiences of psychological services. Studies show that increased race related stressors over time increase the likelihood a person will experience psychological distress. Research also suggests that the personal biases of mental health service providers may impact their competencies and success rate when working with Black and Multi-ethnic clients. In this study, semi-structured interviews were conducted with 10 Black or Multi-ethnic participants who had recently engaged in psychological therapy in Ireland. Data were analysed using the Generic Descriptive Interpretive Qualitative Research Analysis (GDI-QR) approach (Elliott & Timulak, 2021). All participants shared lived experiences of negative mental health implications of being racialised. These were expressed as feelings of not belonging, experiences of racism or discrimination, feeling silenced by cultural and social stigma, and feeling inequitably burdened compared to their white peers. Participants typically reported barriers to access as conflicting values between cultures, previous negative experiences, waitlists, lack of previous knowledge of mental health, and inadequate services for Black service users. Barriers to engagement were mismanagement of racial dynamics and a perceived lack of attunement between service provider and client. Conversely, participants also spoke of growth promoting therapy experiences that strengthened the therapeutic bond. Suggestions for change include adjustment to practice and training for psychologists, in addition to suggestions that could increase accessibility to services for Black and Multi-ethnic service users.